2022
DOI: 10.7717/peerj-cs.1000
|View full text |Cite
|
Sign up to set email alerts
|

Water quality prediction in sea cucumber farming based on a GRU neural network optimized by an improved whale optimization algorithm

Abstract: Sea cucumber farming is an important part of China’s aquaculture industry, and sea cucumbers have higher requirements for aquaculture water quality. This article proposes a sea cucumber aquaculture water quality prediction model that uses an improved whale optimization algorithm to optimize the gated recurrent unit neural network(IWOA-GRU), which provides a reference for the water quality control in the sea cucumber growth environment. This model first applies variational mode decomposition (VMD) and the wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…GRU computations share similarities with the hidden states in standard RNNs. In a GRU, the previous hidden state h t−1 has the same dimensions as the reset gate (Yang and Liu, 2022). After computing the candidate hidden state, the prior hidden state information is transferred to the current hidden state through the update gate.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…GRU computations share similarities with the hidden states in standard RNNs. In a GRU, the previous hidden state h t−1 has the same dimensions as the reset gate (Yang and Liu, 2022). After computing the candidate hidden state, the prior hidden state information is transferred to the current hidden state through the update gate.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…Supplementing average value [16,17], linear interpolation [17,18], KNN [19,20] Dimensionality reduction PCA [8], pooling layer [21], t-SNE [22], SPCA [23] Removing outliers Pauta criterion [18], EWMA [24] Feature selection PSO [1], LASSO [8,25], ASO [26], GA [27], MI [28], GRA [29], PCC [30], CCA [31] Decomposition EMD [32], EEMD [33], CEEMDAN [19,27,[34][35][36][37][38], ICEEMDAN [39], SSA [40,41], VMD [42], SVMD [43] Normalization [6,17,20,27,30,31,34,42,[44][45][46][47][48][49]…”
Section: Missing Valuesmentioning
confidence: 99%
“…Sen et al [57] used a grid search to find the number of nodes in each layer and the number of layers in CNN and LSTM networks when designing the network architecture. Yang and Liu [35] used an improved whale optimization algorithm to optimize the number of layers and nodes in the GRU algorithm for water quality prediction. The results showed that the proposed model could outperform the original GRU model.…”
Section: Network Architecture Selectionmentioning
confidence: 99%
“…GRU may be presented as a spinoff of LSTM [26], a type of RNN. Although GRU is lucid and more compact than LSTM, not only the competency in mastering context is not omitted, but on the contrary, reducing the training time [27] [28]. Alluded to research conducted by [6] as well as [8] [9] [10] on predicting COVID-19 mRNA vaccine degradation rate, it is deduced that GRU is indeed an applicable algorithm for this bioinformatics-related artificial intelligence-based research.…”
Section: Gated Recurrent Unit (Gru)mentioning
confidence: 99%